Symbiotic performance of pasture legumes with naturalised soil rhizobia - Ballard R.A.; Charman N.; Craig A.D.; Hughes S.J. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Most Australian soils contain large and diverse populations of naturalised rhizobia for the pasture genera of Medicago and Trifolium. This paper examines the performance of several pasture legumes with these soil rhizobia. The selection of medics and clovers, better able to form an effective symbiosis with soil rhizobia, is proposed as a way of significantly improving nitrogen fixation in the field.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)